1990
DOI: 10.1620/tjem.161.101
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependency of intratracheal elastase-induced changes in pressure volume curve and morphometry in rat lungs.

Abstract: We studied the dose-dependency of the lung pressure-volume curve (n -37) and morphometry (n -30) with intratracheally administered elastase. Four weeks after elastase was instilled at dosages of 20 (EL-20), 40, 80, and 100 U/100 g wt., chord compliance between 50 and 70% of total lung capacity (TLC) (C5o-70) and that between 80 and 100% TLC (C8o-100) Were measured. After a significant initial reduction, the weight of the EL-80 group recovered to the control level, whereas the weight curve of the EL-100 signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…From these results, we concluded that 80 U·100g -1 BW is optimal for a rat emphysema model produced by a single intratracheal instillation of porcine pancreatic elastase. With 80 U, mean linear intercept was 98 µm, 1.4 times that of the control value, 72 µm [10]. This degree of widening of alveolar space corresponds to human emphysema ranging from mild to relatively severe [23].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…From these results, we concluded that 80 U·100g -1 BW is optimal for a rat emphysema model produced by a single intratracheal instillation of porcine pancreatic elastase. With 80 U, mean linear intercept was 98 µm, 1.4 times that of the control value, 72 µm [10]. This degree of widening of alveolar space corresponds to human emphysema ranging from mild to relatively severe [23].…”
Section: Discussionmentioning
confidence: 85%
“…In earlier work, we tested dose dependency of lung pressure-volume curve and morphometry using porcine pancreatic elastase ranging from 20-100 U·100g -1 BW in rats [10]. The pressure-volume curve at 100 U was more to the right and downward than at 80 U and, in addition, animal mortality shortly after instillation was higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation